Pharmacokinetics of mavacoxib in the New Zealand white rabbit - Wilson, Sarah Elizabeth (Kansas State University, 2022)
Mavacoxib, a selective COX-2 non-steroidal anti-inflammatory drug used for management of osteoarthritis and other inflammatory conditions in dogs, could be very advantageous in zoological medicine patients because of its long plasma half-life (Cox 2010, Lees 2015). The purpose of this study was to characterize the pharmacokinetics of mavacoxib in rabbits and to describe any clinicopathologic effects seen with this dosing. Six healthy, 4-month-old New Zealand white rabbits (3 male, 3 female) were administered 6 mg/kg mavacoxib orally (PO) once. Before drug administration, clinicopathologic samples were collected for baseline data (CBC, biochemistry, and urinalysis), as well as at set time intervals to compare to baseline. Plasma mavacoxib concentrations were determined using liquid chromatography with mass spectrometry, and pharmacokinetic analysis was performed using noncompartmental methods. Following a single PO dose, mean peak plasma concentration (C[subscript max]) was (mean; range) 854.6 (713.2-1040.7) ng/mL; mean time to peak plasma concentration (T[subscript max]) was 0.36 (0.17-0.50) d; mean area under the curve (AUC[subscript all]) was 2000 (1765-2307) d*ng/ml; mean terminal half-life (T[subscript 1/2]) was 1.63 (1.30-2.26) d; and mean terminal rate constant (L[subscript z]) was 0.42 (0.31-0.53) d. Complete blood count, biochemistry, urinalyses, and urine protein:creatinine all remained within published normal reference intervals. Further research is needed to make a dosing recommendation, including a pharmacodynamics study and investigating pharmacokinetics at different doses and multiple doses. Based on this study, it was determined that plasma levels reached target levels of 400ng/mL for 48 hours in 3/6 rabbits, with 3/6 being 10.8-56.8 ng/mL under the target level at 48 hours, when given 6 mg/kg orally once.
Keywords: Pharmacokinetics; Oryctolagus cuniculus; Analgesia; Nonsteroidal anti-inflammatory drug; Rabbit; Mavacoxib